Dimensions of the sacred : an anatomy of the world's beliefs - Smart, Ninian, 1927-2001. (Berkeley : University of California Press, 1996)
This extraordinary book, the result of twenty-five years of reflection and research, is nothing less than a comprehensive examination of how what is spiritual or sacred to humans - both conventionally religious beliefs and those we usually think of as secular - manifests itself around the world. Dimensions of the Sacred for the first time maps the underlying features of the world's major faiths - Christianity, Islam, Judaism, Hinduism, Buddhism, Taoism, Confucianism, and African and other indigenous religions. This would be remarkable in itself. But Ninian Smart then uses the same principles to investigate "secular religions" such as Marxist-Leninism and nationalism.
Smart identifies seven similarities uniting these systems of belief. Whether religious or secular, all world views have elements of ritual - worship, meditation, pilgrimage, and sacrifice - and an edifice of doctrine and philosophy. All world views likewise share a mythic dimension that uses fictional and historical narratives to present and interpret the present. All possess an experiential or emotional dimension giving weight to the visionary experiences of prophets, mystics, and shamans. And all demonstrate an ethical or legal aspect - the Torah in orthodox Judaism, Shari'a in Islam, the Four Noble Truths in Buddhism, and the honorable ideal in Confucianism.
Smart also explores the organizational and social components of sacred belief - the many ways people organize spiritually through institutions, such as church, sect, and caste. He concludes by surveying the artistic and material dimension, uncovering the various ways religions and world views express themselves in material creations such as temples, catherals, chapels, mosques, tombs, icons, pulpits, statues, and books.
Includes bibliographical references (p. [299]-311) and index.
Keywords: Religion